Contributions from the change laboratory to the analysis and prevention of accidents' model - Hurtado, Sandra Lorena Beltran; de Gouveia Vilela, Rodolfo Andrade; de Almeida, Ildeberto Muniz [UNESP]; Filho, José Marçal Jackson; Querol, Marco Antonio Pereira; Simões, Raoni Rocha; Diniz, Eugenio Paceli Haten; Lopes, Manoela Gomes Reis; da Silva, Alessandro José Nunes; Gomes, Marcos Hister Pereira; Costa, Susana Vicentina (Springer Nature, 2019)
Analysis and Prevention of Accidents' Model (MAPA) was structured with the objective of replacing old practices that condemn work accidents on the victim. Applied to different activities, MAPA was able to explain accidents as a product of multiple interacting factors. However, a few changes have been implemented on underlying conditions. Overall, the agency was limited to the teams carrying out the analysis. In order to address this limitation, an interdisciplinary group participated in three workshops intended to reconstruct and improve the MAPA by using the principles of the Change Laboratory (CL). This chapter aims to present a new model of activity system of analysis and prevention of work accidents. The text aims to answer the question: what are the new dimensions brought in from MAPA's development? We will present the stages and challenges of the new model.